Quality by design (QbD) approach in processing polymeric nanoparticles loading anticancer drugs by high pressure homogenizer. Issue 4 (April 2020) - Soni, Govind; Kale, Ketaki; Shetty, Saritha; Gupta, M.K.; Yadav, Khushwant S.
Abstract: Polymeric nanoparticles prepared using high pressure homogenizer (HPH) present some unique challenges during manufacturing which can be better understood by application of quality by design (QbD) approaches. The present review highlights the ways to identify the critical material attributes which includes the anticancer drugs, polymers, surfactants, solvent system and dispersion system. A comprehensive understanding of the critical processing parameters like pressure and number of cycles during the working of HPH used in putting forward the critical quality attributes such as size, shape, surface charge or droplet stabilization. Such QbD approach will involve development of an effective control strategy for would ensure safe encapsulation of anticancer drugs for successful product development. Proper addressing of the issues related to scaling-up would lead to successful commercialization of the nano-sized formulations loaded with anticancer drugs. Abstract : QbD; Polymeric nanoparticles; Anticancer drugs; High pressure homogenizer; Nanotechnology; Nanomaterials; Pharmaceutical science; Cancer research; Oncology